Measuring mitochondrial nonenyzmatic lysine acetylation - Reisenauer, Keighley (My University, 2017)
Protein acetylation is a regulatory modification affecting numerous biochemical and cellular processes. Over half of the proteins in mitochondria have been identified as acetylated, however mechanism of acetylation has not been elucidated. This project focuses on understanding the mechanism of mitochondrial protein acetylation, hypothesizing that non-enzymatic acetylation is responsible for the majority of observed acetylation. To understand non-enzymatic acetylation, we are quantifying the rates of the reaction as a function of acetyl-CoA concentrations, and calculating the second order rate constant for individual lysine reactivity in native proteins. This study will focus on the acetylation mechanism for the following mitochondrial proteins: ACAT, PDH, HMGCS2, HMGCLl, and alphaKGDH, which are reported in scientific literature to be highly acetylated in mouse tissues.